The Paleogene multi-phase tectono-sedimentary evolution of the syn-rift stage in the Nanpu Sag, Bohai Bay Basin, East China. Issue 6 (November 2018) - Jin, Siding; Cao, Haiyang; Wang, Hua; Chen, Shanbin
The Bohai Bay Basin is the second largest oil-producing basin in China located on the east Asian margin. The Bohai Bay Basin contains numerous depressions, sub-basins, and sags. One of these, the Nanpu Sag, has played a particularly important role in oil and gas exploration in recent years. Four depositional systems are recognized in the Nanpu Sag, fan-delta, braided-river delta, turbidite deposits, and lacustrine systems. In the Paleogene, the Nanpu Sag underwent complex and multi-phased rifting evolution. Two evolutionary phases have been identified: the syn-rift phase and the post-rift phase, the syn-rift stage can be further sub-divided into four episodes. This study reveals the considerable faulting activity and associated strong subsidence that occurred during the deposition of the Dongying Formation in the fourth episode of the syn-rift stage. The depositional systems and the tectonic activity during the fourth episode in the Nanpu Sag have very different characteristics compared to those of other depressions or sub-basins in the Bohai Bay Basin. Boundary fault activity was extremely intense during the deposition of the Dongying Formation, especially the east to west trending faults, including the Xinanzhuang Fault and the Gaoliu Fault. Moreover, the migration of subsidence centers from the Shahejie Formation to the Dongying Formation is a result of the strong down-warping that occurred during the fourth episode of the syn-rift stage. In the Nanpu Sag, the Dongying Formation is of great significance to hydrocarbon exploration, which is affected by both the intensity of fault activity and magnitude of basement subsidence.